Strategi Manajemen Islami Untuk Keberlanjutan BMT Di Era Digital: Studi Literatur - Akmal Syawqi Albar; Dedy Rachmad; Aslichan (Rayah Al-Islam, 2025)
Baitul Maal wa Tamwil (BMT) is pivotal to Islamic financial inclusion and MSME resilience; however, digital disruption, financing risks, and governance gaps challenge its sustainability. A clear sustainability strategy is crucial for BMT's competitiveness and its contribution to the national Islamic finance agenda. This study formulates an integrated Islamic management framework to strengthen BMT sustainability in the digital era. An integrative literature review (2021–2025) with thematic synthesis was employed. Sources include peer-reviewed national/international journals, as well as pertinent regulations. Studies were identified through keyword searches ("BMT," "digitalization," "Islamic management," "risk management," "human capital," "maqasid al-shariah"), screened at the title/abstract level, and their full texts assessed, coded, and synthesized across five themes. (1) Islamic governance grounded in tawhid–amanah–'adl–ihsan, strengthened by Sharia Supervisory Boards and SAK-EP, enhances accountability and trust. (2) Digital solutions—mobile apps, sharia e-wallets, lean core banking, and big-data analytics—improve efficiency and access despite literacy/infrastructure constraints. (3) Islamic risk management using partnership contracts, financing diversification, and digital credit scoring helps reduce NPF. (4) Human-capital upgrading—fiqh muamalah, digital literacy, and Islamic leadership—builds a productive and ethical culture. (5) Maqasid al-shariah integration balances financial, social, and spiritual objectives. The study integrates five critical pillars into a cohesive, operational framework for BMT sustainability—an approach that has not been comprehensively articulated in prior works. Managers should institutionalize Islamic governance, scale prudent digitalization, and invest in capacity building. Regulators/local governments are advised to provide incentives, infrastructure, and consumer-protection standards. The proposed framework offers actionable guidance and a policy basis to bolster Islamic microfinance competitiveness.